The Impact of Digitalization on Strategic Management: A Bibliometric Analysis of Technology Integration in Strategic Decision Making - Judijanto, Loso; Hafidurrahman, Moh.; Sari, Efti Novita; Hanafi, Suriah (Westscience Press, 2023)
This research conducts a comprehensive bibliometric analysis to explore the impact of digitalization on strategic management, with a specific focus on the integration of technology in strategic decision-making. The analysis spans the years 2002 to 2023, incorporating peer-reviewed articles and conference papers from prominent databases such as Scopus, Web of Science, and PubMed. The study employs citation analysis, co-citation analysis, and keyword analysis to uncover influential works, thematic clusters, and prevalent research themes within the literature. Key findings reveal a steady increase in publications over the past two decades, indicative of the growing scholarly interest in the intersection of digitalization and strategic decision-making. Seminal works, including